2016
DOI: 10.1021/acs.est.5b05603
|View full text |Cite
|
Sign up to set email alerts
|

How to Determine the Environmental Exposure of PAHs Originating from Biochar

Abstract: Biochars are obtained by pyrolyzing biomass materials and are increasingly used within the agricultural sector. Owing to the production process, biochars can contain polycyclic aromatic hydrocarbons (PAHs) in the high mg/kg range, which makes the determination of the environmental exposure of PAHs originating from biochars relevant. However, PAH sorption to biochar is characterized by very high (10(4)-10(6) L/kg) or extreme distribution coefficients (KD) (>10(6) L/kg), which makes the determination of exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
58
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 39 publications
3
58
0
1
Order By: Relevance
“…Because of this health risk, many efforts were devoted to understand or reduce the total and bioavailable PAHs inside the biochars (Sharma and Hajaligol 2003;Zielinska and Oleszczuk, 2016). On the other hand, after biochars were applied in strongly PAHs contaminated soil, they often act as a sink to adsorb PAHs rather than as a PAHs releasing source (Mayer et al 2016). The application of EngBCs can even further reduce the ecotoxicity of PAHs contaminated soils and the reduction efficiency depends on the method of modification.…”
Section: Dissolvable Contaminantsmentioning
confidence: 99%
“…Because of this health risk, many efforts were devoted to understand or reduce the total and bioavailable PAHs inside the biochars (Sharma and Hajaligol 2003;Zielinska and Oleszczuk, 2016). On the other hand, after biochars were applied in strongly PAHs contaminated soil, they often act as a sink to adsorb PAHs rather than as a PAHs releasing source (Mayer et al 2016). The application of EngBCs can even further reduce the ecotoxicity of PAHs contaminated soils and the reduction efficiency depends on the method of modification.…”
Section: Dissolvable Contaminantsmentioning
confidence: 99%
“…In the case of biochars from wood, the levels of non-BCHyPy PAHs were much larger suggesting that their application in soil can contribute significantly to this fraction of organic carbon. PAHs can pose a short or long-term threat to soil and the environment by influencing the soil microbial activity [32], increasing in some case the persistence of mobile PAHs [59]. Therefore, the evaluation of the non-BCHyPy fraction as a potential source of mobile PAHs is an important environmental aspect.…”
Section: 3 Non-bchypy Fractionmentioning
confidence: 99%
“…Jindo et al [26] reported a higher diversity of fungi in biochar-amended compost. Biochar materials strongly sorb polycyclic aromatic hydrocarbons (PAHs) and are thus characterized by very high sorption coefficients (K D ) for PAHs [27].It was also reported that the N loss was mitigated by adding FGD gypsum to composting materials [28,29]. Flue gas desulphurization gypsum (FGD gypsum) is a by-product of wet gas desulphurization in coal-fired power stations and generally has a high purity, low heavy metal content, and is rich in essential mineral nutrients for plants such as S, Si and Ca [30,31].…”
mentioning
confidence: 99%
“…Jindo et al [26] reported a higher diversity of fungi in biochar-amended compost. Biochar materials strongly sorb polycyclic aromatic hydrocarbons (PAHs) and are thus characterized by very high sorption coefficients (K D ) for PAHs [27].…”
mentioning
confidence: 99%